Estimates of the best bilinear approximations for the classes of (ψ,β)-differentiable periodic multivariate functions - Shvai, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
Order estimates are obtained for the best bilinear approximations of 2d-variable functions f(x y), x, y π_d, π_d =^d_j=1 [ π , π ], formed by d-variable functions f(x) L^ψ_β ,p by the shifts of their argument x π_d by all possible values of y π_d in the space L_q_1,q_2 (π 2d). The results include various relations between the parameters p, q_1 and q_2.